Method for laparoscopic transgastral resection for mesenchimal gastric tumors - A. K. Kamalov; A. B. Ryabov; V. M. Khomyakov; N. N. Volchenko; I. V. Kolobaev; A. K. Kostrygin; S. A. Aksenov (Сибирский онкологический журнал)
The purpose of the study was to evaluate the efficacy and safety of laparoscopic transgastric resection for mesenchymal tumors of the proximal stomach.Material and Methods. A retrospective-prospective study was carried out. Surgical techniques of laparoscopic transgastric resection and the history of the development of this surgical method were described in detail. A total of 11 laparoscopic transgastric resections were performed. The course of the postoperative period and the postoperative management of patients were described. The immediate and long-term results of surgical treatment and the quality of life of patients were presented.Results. The assessment of the quality of life of patients after surgery showed that there were no cases of gastroesophageal reflux disease compared to proximal subtotal resection of the stomach or endoscopic tunnel resection. All patients underwent radical resection. In our study, we did not encounter cases of conversion of the surgical approach, as well as serious postoperative complications (Clavien–Dindo>III ). The analysis of long-term treatment outcomes showed that there were no cases of recurrence or disease progression. All patients are alive and followed up.Conclusion. This technique is fully justified, with careful selection of patients and compliance with all the rules of surgical oncology. Transgastric resection of gastric mesenchymal tumors located in the region of the cardioesophageal junction is a justified and safe technique. Surgery is performed under clear visual control, EGDS is not required to detect the tumor. This method allows the reduction of the frequency of contamination of the gastric flora into the abdominal cavity as well as the reduction of the wound area of the anterior abdominal wall.